Konsep Mitigasi Bencana pada Kawasan Wisata Kuliner Terapung Torangen di Kota Pare - Pare - Agung Imam Kurniawan; Naidah Naing; Ansarullah Ansarullah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
This study develops a floating culinary tourism area in Tonrangeng Riverside, Parepare, as an innovative solution to overcome mainland land limitations and maximize tourism potential. A descriptive analytical qualitative method was applied, with the collection of primary data (observation, interviews) and secondary data (literature studies, regulations). The results formulated an integrated zoning system (Culinary, Entertainment, Relaxation, Transportation) that is efficient and responsive to the natural characteristics. The architectural design adopts biomimicry principles of butterfly morphology using corrosion-resistant composite materials, creating an aesthetic and functional visual identity. Crucially, this research integrates a comprehensive disaster mitigation system comprising adaptive floating structures, flexible mooring systems, dedicated evacuation routes, and real-time monitoring, thus creating a safe, comfortable, and sustainable destination. This model complies with national regulatory standards and can serve as a prototype for similar development in other coastal areas of Indonesia.